TONES OF STEVE JOB'S GOODBYE SPEECH - Yena Aulia Rusilawati; Acep Haryudin; Efransyah Efransyah (IKIP Siliwangi, 2019)
This article is an analysis study of tone in a speech, and this analysis based on the theory by Michael McCarthy and Crystal. The article is aimed to know about kinds of tones, the dominant tones and the meaning of dominant tones in the speech. The writers found that this speech used five kinds of tones, namely Rise, Fall, Fall-rise, Rise-fall and level. The result showed all answer of the question. In this article we can know the meaning from the speaker in his speech, how is his feeling and his expression just from their tones in speaking that is Steve job’s showed how Steve Job’s is Encouragement, Urgency and Straight (positive face) because the dominant types of tone he used in his speech is Fall-rise. In the video showed. The writers suggests for the further writers can use other sources which are more than interesting from this one.